ATRIAL FIBRILLATION AND CHRONIC HEART FAILURE: PRACTICAL ASPECTS AND DISCUSSION ISSUES OF RATIONAL PHARMACOTHERAPY - Yu. А. Bunin; S. V. Miklishanskaya (Рациональная фармакотерапия в кардиологии, 2017)
Atrial fibrillation (AF), being both a cause and a consequence of chronic heart failure (CHF), occurs with it significantly more often than in the general population. Prevention and treatment of AF in patients with CHF has its own specifics and presents certain difficulties for practical physicians of various specialties. The article presents a modern view of primary and secondary prevention of AF in patients with CHF and a critical analysis of international recommendations on the use of various antiarrhythmics and not antiarrhythmic drugs, anticoagulants and non-drug treatments in these patients. Based on the analysis of a number of studies, it has been shown that in patients with AF and CHF, the sinus rhythm control strategy has no advantages over the rate control strategy. The review also examines the possibilities of drug therapy in rate control strategy in CHF, depending on the size of the left ventricular ejection fraction, as well as indications for interventional prophylaxis of the AF paroxysms. At the same time, it discusses some questions about the choice of tactics for management of patients with AF and CHF, electrical and pharmacological cardioversion and prevention therapy, features of AF treatment in certain diseases and syndromes. The article also presents a critical evaluation of interventions in the treatment of AF, such as catheter ablation of AF, catheter ablation of additional routes and destruction of the AV node in combination with the pacemaker implantation.